Advances in Animal Aging Models - YIN Danyang; HU Yi; SHI Rengfei (Shiyan dongwu yu bijiao yixue, 2023)
With the increasing severity of global aging, aging-related issues have become the hotspot in the field of health. In recent years, animal aging models have been widely developed and applied, which is of great significance in the study of aging mechanism. Animals with short life span, such as Caenorhabditis Elegans and Drosophila Melanogaster, have natural advantages in the study of aging. Various rat and mouse aging models have been used in aging studies. In recent years, new animal aging models have been developed, such as the African turquoise killifish. The authors reviewed main animal models used in the study of aging, and analyzed the establishment methods, evaluation indexes, advantages and disadvantages of each model in order to provide reference for related research.